Factors Associated with Suicide in Four Age Groups: A Population Based Study. Issue 1 (2nd January 2018) - O'Neill, S.; Ennis, E.; Corry, C.; Bunting, B.
Abstract : Life events and circumstances leading to death change throughout the life course. In this study, 4 age groups within those who have died by suicide are compared in terms method of suicide, sex, occupation, mental disorders, prior suicide attempts, and life events prior to death. Analyses were based on a database of deaths by suicide and undetermined intent based on data in the Northern Ireland (NI) coronial files from 2005–2011 (N  = 1667). Research determined that hanging is very prominent as a method of death within the under-20 age group. Women who die by suicide are more likely to have a known mental disorder than men, and the proportions increase with age group. Relationship difficulties are associated with many of these deaths and particularly for males aged under 40 years. Physical health and life events were more relevant than mental illness per se, in males aged over 61 years. For a sizeable proportion of the cases included in the current database there was no information on the life events prior to death. Understanding the factors associated with suicide across age groups is essential to informing suicide prevention strategy and programs and the development of more nuanced and effective interventions.